Optimizing microwave-assisted extraction of ursolic acid from apple pomace using response surface methodology - Sun, Xiyun; Zhang, Wenjian; Meng, Xianjun; Shokri, Sajad (Frontiers in Nutrition, 2025)
This study investigates the optimization of microwave-assisted extraction (MAE) to recover ursolic acid (UA) from Hanfu apple pomace using response surface methodology (RSM). The effects of three key variables—extraction time, sample-to-solvent ratio, and ethanol concentration—on UA yield were studied. A Box-Behnken design was employed to model and optimize these variables. The results showed that extraction time had the most significant effect on UA yield, followed by ethanol concentration and sample-to-solvent ratio. The optimal conditions for UA extraction were 118.25 s for extraction time, a 1:30.86 sample-to-solvent ratio, and 82.23% ethanol concentration, with a predicted maximum UA yield of 89.92%. These results were validated with an actual UA yield of 88.87%, confirming the model's predictive reliability. The study highlights the efficiency of MAE for extracting UA, demonstrating its potential as a green extraction method for bioactive compounds from apple pomace. Further purification using XAD-7 resin improved UA purity significantly.